PENERAPAN SANKSI DENDA ATAS PUTUSAN KPPU TERHADAP PUTUSAN PIDANA KORUPSI SEBAGAI DASAR ULTIMUM REMIDIUM - Murtadho, Achmad; Sylvia Mufarrochah; Febri Falisa Putri; Elsa Assari (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
This research aims to analyze the application of fine sanctions for KPPU decision Number: (04/KPPU-I/2021) for Decision Number 28/Pid.Sus-TPK/2021/PN Jkt Pst, due to sanctions against evidence in the District Court Decision Central Jakarta Corruption Crime Number 28/Pid.Sus-TPK/2021/PN Jkt Pst is forfeited to the State, so the fine sanctioned by the KPPU Council is Zero. The method used is normative juridical research. The results of this research show that the KPPU KPPU prioritizes the administrative approach over the criminal approach. Although according to the law, a violation only has a criminal element if the violation that occurs is dangerous to the capital market or the public interest.